Association Between Menstruation Knowledge and Attitudes Toward Gender Norms Among Female Adolescents in Rural Nigeria: Analysis of AGILE-IE 2023 - Zuhrotunida Zuhrotunida; Hikmah Hikmah; Catur Erty Suksesty; Abubakar Yakubu Abbani (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
Despite heightened global focus on menstrual health and gender equality, adolescent girls in rural Nigeria still encounter significant deficiencies in knowledge and attitudes. Misinformation and cultural taboos regarding menstruation perpetuate negative gender norms, thereby constraining the empowerment and participation of girls. This study examines the relationship between adolescent girls' menstrual knowledge and their attitudes toward gender norms in rural areas of three northern Nigerian states. This is a cross-sectional study that utilized secondary data from the World Bank’s AGILE Impact Evaluation 2023, with a sample of 8,188 in-school adolescent girls aged 15–20 from Kaduna, Kano, and Katsina States in northern Nigeria. Univariate, bivariate, and multivariate analyses were conducted to examine the relationship between knowledge of menstruation and gender attitudes, controlling for religion, state, place of residence, and boarding school attendance. Good menstrual knowledge was found to be very poor among the adolescent girls (2.80%), and their gender attitudes were also abysmal (96.91%). Adolescent girls possessing good menstrual knowledge demonstrated an almost twofold likelihood of exhibiting positive gender attitudes (AOR = 1.99; 95% CI: 1.13–3.51, p = 0.018). Muslim adolescents, as well as those residing in Kano and Katsina states, exhibited a notable decrease in the likelihood of possessing progressive gender attitudes. Urban residency correlated with improved gender attitudes, whereas attendance at boarding schools exhibited no notable impact. Poor understanding of menstruation is linked to poor gender attitudes among female adolescents in rural northern Nigeria. Integrating menstrual health education programs with sensitization about gender norms is essential for enhancing girls' empowerment and addressing discriminatory norms. Therefore, policies must consider sociocultural and religious influences that shape adolescent gender ideologies.